Supersonic flow control with quarter rib in a duct: An extensive CFD study - Khan, Ambareen; Aabid, Abdul; Akhtar, Mohammad Nishat; Khan, Sher Afghan; Baig, Muneer (Elsevier B.V., 2025)
A sudden increase in the area of a duct or at the blunt base of the projectile leads to flow separation and reattachment. In the flow separation process, the base pressure at the blunt base is sub-atmospheric, leading to significant drag, which can be around sixty to seventy percent. This study is undertaken to regulate the base pressure in the recirculation zone and the flow field of the duct. This paper focuses on the effectiveness of quarter ribs of various radii in the range from 1 mm to mm and nozzle pressure ratio ranging from 3 to 11 at Mach M = 1.48 for a duct diameter of 22 mm and its sizes ranging from 1D to 6D. Some oscillations are observed for the rib location of 11 mm from the exit of the nozzle. Due to the proximity to the nozzle exit, these oscillations are observed. With a progressive shift of passive control along the more significant length, a continued rise in the pressure in the base region for rib radii in the range from 2 mm to 4 mm and an extreme increase in the base pressure is achieved for 4 mm rib radii placed at 66 mm inside the duct. Nevertheless, despite the maximum enhancement in pressure for duct size L = 4D, a negligible reduction in base pressure and ambient pressure cannot affect the flow contained by the duct for a more considerable duct length. However, using a quarter rib radii of 1mm is inadequate, and base pressure values are identical with and without rib except for the nozzle pressure ratio (NPR) = 3, where the nozzle at NPR = 3 is over-expanded. Except at NPR = 3, the nozzles are under-expanded, and the control mechanism becomes efficient, resulting in a significant base pressure increase. One can make a final decision based on the mission requirements about the radius of the rib, rib location, and level of expansion to meet the user’s requirements.